Gender and residential differences in sleep quality among Chinese adolescents aged 13–18 years - Xuye Kang; Jianying Li; Huipan Wu (PLoS ONE, 2026)
Background Good sleep is essential for healthy adolescent development, yet declining sleep quality among Chinese adolescents has become a nationwide public health concern. Residential setting and sex are key determinants of sleep quality; however, systematic evaluations of sleep quality across regions and between sexes among Chinese adolescents remain limited. Methods Data were collected on Pittsburgh Sleep Quality Index (PSQI), body mass index (BMI), Physical Fitness Index (PFI), sedentary time, screen time, and mental health from 5,713 adolescents (mean age, 15.11 ± 1.70 years). Logistic regression models were applied to examine the effects of these factors on adolescent sleep quality, including interactions with residence and gender. Results Overall, 33.71% of Chinese adolescents exhibited poor sleep quality. The prevalence of poor sleep quality was 35.78% among rural adolescents, which was significantly higher than that among urban adolescents (p < 0.001). Among females, 38.40% were classified as having poor sleep quality, a proportion significantly higher than that among males (p < 0.001). BMI, PFI, moderate-to-vigorous physical activity (MVPA), sedentary time, screen time, and mental health scores were significantly effects on the PSQI global score and its component scores (p < 0.05). Residence and gender significantly moderated the linear associations between sleep quality and BMI, PFI, MVPA, sedentary time, and mental health scores (p < 0.05). Conclusions Chinese adolescents living in rural areas and female adolescents experience a greater burden of poor sleep quality. Mental health and PFI appear to be protective factors for sleep quality, whereas BMI, sedentary time, and screen time are risk factors among Chinese adolescents. Moreover, these associations are moderated by residence and gender.